THE PROBLEMS OF SCIENTIFIC DEFINITION AND CLASSIFICATION OF GENRES IN THE SCIENTIFIC FUND (Heritage, 2021)
Problems of scientific definition and redefinition of terms, consequently, in accordance with the topic of this scientific paper, are also problems of scientific definition of the term genre and classification of genres in the scientific fund. Defining the term genre is an important scientific-cognitive process, that acquires the essential determinants of the term itself, which have a definiendum and definiens; subject and content value, which includes the whole subject and especially the criteria for classification of the term. In this paper, genetic definitions will include the genesis and development of the concept of genre and scientific-theoretical and methodological directions of various sciences and scientific disciplines. According to temporal and territorial determinants, this paper covers a closer scientific-theoretical and methodological past, as well as modern conditions of scientific communities, both from the former SFRY and other European and wider scientific communities and their paradigms.
Keywords: scientific fund, concept, genre, theoretical approaches, classical genre theory, modern genre theory, classification, classification criteria, European tripartite classification of genres, Russian classification of genres, Yugoslav classification of genres, Anglo-American classification of genres